ChemInform Abstract: Bifunctional Thiourea Catalyzed Asymmetric Mannich Reaction Using Trifluoromethyl Aldimine as Trifluoromethyl Building Blocks. Issue 50 (December 2015) - Ji, Shilong; Alkhalil, Ahmed Ebrahim; Su, Yingpeng; Xia, Xiaowen; Chong, Siying; Wang, Ke‐Hu; Huang, Danfeng; Fu, Ying; Hu, Yulai
Abstract: A bifunctional thiourea‐catalyzed asymmetric Mannich reaction using trifluoromethyl aldimine as trifluoromethyl building block affords indanecarboxylates as diastereomeric mixtures (III), each of them with high enantioselectivity.